Last Millennium volcanism impact on the South Atlantic Ocean - Verona, Laura Sobral (2018)
Volcanism is the cause of great non-anthropogenic perturbations on the Earth climate through energy imbalance changes. There is still much to be uncovered relative to its impacts on the Southern Hemisphere, even more with respect to the Southern Ocean. The South Atlantic and its Southern Ocean sector response to volcanism are examined using simulation results from the Last Millennium Ensemble Experiment of the Community Earth System Model (CESM-LME), for the period 850-2005. Composite results point to significant changes in sea surface temperature and salinity in the first austral summer following the eruption. North of 60S, there is ocean cooling, as expected because of the higher albedo related to the volcanic forcing. In contrast, near the Antarctic Peninsula in the Weddell Sea, a local warming of ∼ 0.8ºC is observed (significant at the 90% level). Salinity shows positive anomaly (∼0.1) at the northern region off Antarctic Peninsula from the first year after the eruption to the fourth subsequent year. Oceanic surface anomalies weaken after the fifth subsequent year, however it is still present in deeper layers (∼500m). At the same time, wind stress changes are evident, results show a poleward shift (∼2º), strengthening (∼10%) of the prevailing westerlies and the reversal in direction of the meridional wind stress component in the northern Antarctic Peninsula. As consequence, there is intensification of the Antarctic Circumpolar Current southern extension. Together with the stronger westerlies, the mixing in the northern Antarctic Peninsula is enhanced, bringing up warmer subsurface waters, therefore explaining the anomalous surface warming after the eruption. The 1991 Mt. Pinatubo eruption response is also investigated. CESM-LME, observations and reanalysis have shown similar behavior, however for the second subsequent year, thus suggesting the occurrence of the same mechanism identified after Last Millennium eruptions.